History of Russian Translational Reception of Edwin Arnold’s Poem “The Light of Asia”: Translation by A.M. Fedorov - V. V. Serdechnaya; D. N. Zhatkin (Научный диалог, 2025)
This study investigates the translational strategies employed by A.M. Fedorov in his poetic rendition of Edwin Arnold’s Buddhist poem “The Light of Asia,” created in 1895. It explores how Arnold’s text is modified in translation and how these modifications contribute to the contextualization of the poem within the Russian poetic landscape. The analysis draws on the original text of “The Light of Asia” by Edwin Arnold, along with translations by A.N. Annenskaya, I.M. Sabashnikov, and A.M. Fedorov, as well as literary-critical publications from the turn of the 19th to the 20th century. Employing historical-literary and comparative approaches, the study aims to analytically explore the transformations of Arnold’s text within Russian culture. It is reported that A.M. Fedorov creates his poetic adaptation of Arnold’s work based on Annenskaya’s earlier prose translation (1890). The findings reveal that he modifies the meter of the original and significantly varies it, replacing the unrhymed pentameter with a diverse range of rhymed forms, typically aligned with the tradition of Russian Oriental poetry. Furthermore, it is shown that Fedorov Russifies the translation in terms of vocabulary and stylistically aligns it with Romantic traditions, allowing for considerable deviations from the original, including omissions and additions. Notably, the ease of the verse and the familiarity of the poetic form contribute to the popularity of this translation in Russia at the turn of the 19th and 20th centuries; it has been reedited and republished in the early 21st century.